Role of bank financing and progressive green growth in Indonesia - Qoriah, Ciplis Gema; Nasir, M.Abd; Irkham, Bagus Maulana (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
Green growth is an essential issue for many countries due of climate change and global warming. The complexity of environmental problems is increasing along with the rate of economic growth that ignores ecological sustainability. The financial sector is of key supporting factor for green growth. Likewise, Indonesia, as a developing country, requires the financial sector to play of role in achieving sustainable green development. This study aims to analyze the banking performance sector and green growth in Indonesia during the period 1990Q1-2023Q4. This study uses time-series data and the Vector Error Correction Model (VECM) to analyse the data. The results of the analysis show that the banking performance sector has a positive and significant influence on green growth in both the short and long terms.